Paediatric Sudden Sensorineural Hearing Loss: Pooled Analysis and Systematic Review - Reading, Jacob C. S. (J Int Adv Otol, 2021)
Sudden sensorineural hearing loss (SSNHL) is defined as hearing loss of ≥30 dB in one or both ears, developing within 3 days, affecting ≥3 contiguous frequencies. It is rare in children, but if untreated can cause significant morbidity. During the critical developmental period, it may cause lifelong social, behavioral, and mental sequelae. Currently, little guidance exists on prognosis and management within a pediatric population. A systematic literature review of pediatric SSNHL on PubMed, EMBASE, and the Cochrane CENTRAL database was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations. A total of 620 papers met the Medical Subject Headings criteria, of which 14 met analysis criteria—13 were level 4 and 1 was level 2b evidence. A population of 732 individuals was analyzed. Most reported cases of pediatric SSNHL were idiopathic. Other etiologies included viral infection, trauma, ototoxic drugs, and structural abnormalities. Recovery was defined as any improvement in hearing after the initial loss, from “slight” to “complete.” Recovery ranged from 20% to 100%, with a pooled rate of 56%. Systemic steroids were the mainstay of treatment, although salvage intratympanic steroid therapy had a role after the failure of systemic steroids. Children with bilateral SSNHL had poorer outcomes than those with unilateral loss, with 29% showing improvement. Two studies reported outcomes with no treatment, for which recovery rate was 7%. This analysis of SSNHL shows that 61% of children with unilateral and 29% of children with bilateral SSNHL demonstrate some recovery, a worse prognosis than adults. Multiple treatment regimens exist, although comparison is challenging owing to inconsistently reported improvement parameters.